Effect of high intensity ultrasound on physicochemical, interfacial and gel properties of chickpea protein isolate. (July 2020) - Wang, Yuntao; Wang, Yingjuan; Li, Ke; Bai, Yanhong; Li, Bin; Xu, Wei
Abstract: In order to improve the functional properties of chickpea protein isolate (CPI), CPI was treated with high intensity ultrasound (HIU) at a frequency of 20 kHz under 300 W for different time. Then the functional properties were evaluated, and the structure was analyzed to illustrate the mechanism. It was found that the solubility of CPI significantly ( p = 0.000138, < 0.05 ) increased from 7.5 mg/mL to 9.5 mg/mL, and the foaming capacity of CPI increased to a maximum value of 136.7%, which was 2.2 times that of the untreated group. The emulsifying index of CPI slightly ( p = 0.000017, < 0.05 ) increased from 22.3 m 2 /g to 24.17 m 2 /g. Moreover, the water holding capacity and breaking force of the heat induced CPI gel significantly increased from 58.4% to 80.9% ( p = 0.000004, < 0.05 ), and 78.1 g–201.4 g ( p = 0.000024, < 0.05 ), respectively, which were probably due to the gradually increased free sulfhydryl content, surface hydrophobicity, surface potential and decreased particle size of CPI with extension of ultrasonic time. These results not only demonstrate the relationship between the structure and functional properties of CPI, but also provide a promising way to tailor the functional properties of CPI, which will promote its application in the food industry. Highlights: High intensity ultrasound (HIU) decreased particle size of chickpea protein isolate. HIU improved the emulsifying and gel property of chickpea protein isolate (CPI). The solubility of CPI increased by 26.7% after HIU treatment. HIU remarkably improved the foaming capacity of CPI from 62.1% to 136.7%. HIU increased the surface free sulfhydryl content and surface hydrophobicity of CPI.